(untitled) (Revista do CAAP, 2024)
This paper examines the case of Dr. Daniel Karsai, a Hungarian human rights attorney, who suffered from advanced ALS and was seeking euthanasia to die with dignity, in accordance with his spiritual and professional beliefs. However, Hungarian law prohibits euthanasia and imposes extraterritorial jurisdiction, risking prosecution for those assisting in assisted suicide even if it is practiced abroad. Consequently, Dr. Karsai took his case to the European Court of Human Rights (ECHR), arguing that Hungary’s total ban on end-of-life decisions violates his fundamental human rights, including the right to self-determination, prohibition of inhuman treatment, and freedom of ideological belief. The reasoning presented by Dr. Karsai and by the Hungarian government along with the decision by the ECHR given on June 13, 2024, will be analyzed. The article also explores the Hungarian legal framework’s extraterritorial application, the right to life, the prohibition of torture, and the rights to privacy and freedom of thought under the European Convention on Human Rights. Lastly, using the Brazilian legal framework as an example, it will be argued that the applicant’s justifications may be applicable on a global scale, enabling a new perspective of the legal debate around euthanasia and reflecting on the broader ethical and juridical issues surrounding the right to die with dignity.